Essential Oil Composition and Antibacterial Activity of Alstonia scholaris (flower) from Pakistan (Journal of Agriculture and Biology, 2025)
This study investigated the essential oil composition and antibacterial activity of the flowers of Alstonia scholaris. Microwave-assisted extraction of essential oil was performed, and the extraction process resulted in a 0.218% (w/w) yield. Gas chromatography mass spectrometry (GC-MS) revealed twenty-seven constituents, and confirmation was performed by calculating their retention indices. The most abundant compounds were: 2-Hexenal, (E)- (12.455%), 3-Hexen-l-ol, (Z)- (11.347%), Heneicosane (6.471%), Hexanal (5.913), Tricosane (5.879%), and 2-Methoxy-4-vinylphenol (4.557%). The agar disc diffusion assay was used to determine the antibacterial activity of the volatile oil against Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa, and zones of inhibition were observed against these strains as 11mm, 11mm, 10mm, and 9mm, respectively. The presence of various well-known antibacterial agents shows an obvious relationship with the activity of the essential oil.